Pulgones (Hemiptera: Aphididae) y sus parasitoides (Hymenoptera) en cultivos de sorgo en los estados de Colima y Tamaulipas, México - Rodríguez-Vélez, Beatriz; Suaste-Dzul, Alba; Gallou, Adrien; Rodríguez-Vélez, José Manuel; Sarmiento-Cordero, Mariza Araceli; Arredondo-Bernal, Hugo Cesar (Instituto de Ecología, A.C., 2019)
The sugarcane aphid Melanaphis sacchari and the green aphid Schizaphis graminum, are species that coexist in sorghum crops. The green aphid was reported for Mexico in 1972 in oats and the sugarcane aphid in 2013 in sorghum, causing the last one loss up to 100%. Since then, efforts are underway for their control; therefore, the objective of this study was to find parasitoids associated to M. sacchari and S. graminum in sorghum crops in Colima and Tamaulipas. In Tamaulipas, five localities affected by the sugarcane aphid were sampled in 2014 by collecting parasitized aphids. In Colima the collecting was weekly during a cycle of sorghum, by netting and direct collection, in 2016. Two species of parasitoids were recorded, Lysiphlebus testaceipes where two haplotypes were recognized, one for each state, and Pachyneuron aphidis, hyperparasitoid of L. testaceipes. The green aphid and L. testaceipes showed greater presence during the development of the leaves and beginning of blooming, while the sugarcane aphid was more abundant during the development and filling of the grains, during that stage in the case of sugarcane aphid, the presence of parasitoids was almost null. Concluding that L. testaceipes and P. aphidis show preference for S. graminum in the study area.